2014
DOI: 10.1021/la503631b
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of Phenylalanine in the Presence of Oxidized Carbon Nanotubes

Abstract: Photolyses at 254 nm of phenylalanine (Phe) in aqueous solutions, were carried out in the presence of oxidized carbon nanotubes modified by the reaction with SO2 (mNTO). Kinetics of the photolyses were followed by UV spectrophotometry at 220 nm, and the products were characterized by HPLC, XPS, and (13)C-SSNMR. The ratio of the initial rates of photolysis in the presence and absence of mNTO, k*/ko*, showed a systematic decrease. The photolytic decay of Phe occurs with minor formation of tyrosine. The mass of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…As can be observed in Table , CNTs decreased the rate of the absorbance change of Phe upon photolysis up to 90%. The substantial decrease of the initial rate ratio in the presence of CNT occurred with an associated decrease of the band of Tyr at 295 nm, which was consistent with analysis of the products of the photolysis of Phe by HPLC/MS …”
Section: Results and Discusionsupporting
confidence: 82%
See 2 more Smart Citations
“…As can be observed in Table , CNTs decreased the rate of the absorbance change of Phe upon photolysis up to 90%. The substantial decrease of the initial rate ratio in the presence of CNT occurred with an associated decrease of the band of Tyr at 295 nm, which was consistent with analysis of the products of the photolysis of Phe by HPLC/MS …”
Section: Results and Discusionsupporting
confidence: 82%
“…The values of κ shown in Table indicate that O 2 has only a minor effect on the photolytic decay of Phe in the presence of CNT. It was shown that the disappearance of Phe was not due to adsorption of the amino acid by the CNT while X‐ray photoelectron spectroscopy spectrum and 13 C SSNMR showed the photoinsertion of Phe in the carbon matrix of Humeres et al…”
Section: Results and Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] In all cases, the thiolysis proceeded through the oxidized intermediate, while reaction with amine took place through the primary product episulfide. These results suggest the possibility of a double functionalization of the matrix through an amino-thiolysis reaction if both reactive sites would be near enough as assumed by the primary mechanism.…”
Section: Selective Reactivity Of So 2 Reduction Intermediates Insertementioning
confidence: 99%
“…Several other electrophiles could react, allowing an extensive surface functionalization and generating modified graphenes with miscellaneous physical‐chemical properties. The reactivities of several carbons modified with SO 2 , including MPGO and nanotubes, with respect to the basic hydrolysis, thiolysis, aminolysis, reaction with alkyl halides, and photolysis of phenylalanine and t ‐butanol have already been studied. XPS spectra after the reaction calculated by the atom inventory method, assuming reactions already described in the literature, showed that thiol and t ‐butanol moieties were inserted via oxidized intermediates, while in aminolysis, only the non‐oxidized intermediate was involved.…”
Section: Introductionmentioning
confidence: 99%